A comparative study on crystal violet and congo red dyes removal from wastewater using Trichoderma reesei biomass: Equilibrium, kinetic, thermodynamic studies, and error analysis - Yildiz, Melike Berfin; Bilgi, Mesut; Isik, Birol (ELSEVIER, 2026)
This study examined the adsorption of crystal violet (CV) and Congo red (CR) dyes utilizing Trichoderma reesei biomass. The physicochemical characteristics were examined by FTIR-ATR, SEM, zeta potential, and pHpzctests. The influences of pH, initial dye concentration, temperature, adsorbent dosage, and contact time on biosorption capacity were examined and optimized by a batch experimental approach, subsequently followed by modeling the kinetics, equilibrium, and thermodynamics of the adsorption process. The adsorption isotherm was utilized in multiple two- and three-parameter non-linear isotherm models. The Langmuir model indicated adsorption capacities for CV and CR dyes of 40.35 +/- 2.34 mg/g and 30.44 +/- 1.75 mg/g at 298 K, respectively. Adsorption kinetics indicated that the adsorption adhered to a pseudo-second order kinetic, and the intraparticle diffusion suggested that the process transpired in two stages. Moreover, thermodynamic modeling indicated that adsorption was spontaneous, characterized as an exothermic (Delta Ho = -24.91 kJ/mol) process for CV dye and an endothermic (Delta Ho = 32.02 kJ/mol) process for CR dye. Real wastewater research was undertaken, indicating that T. reesei biomass was successful in diverse aquatic settings. Reusability studies demonstrated that the biomass exhibited significant efficacy until the sixth cycle. Based on the results, T. reesei biomass demonstrated significant efficacy in the adsorption of both anionic and cationic dyes.
Keywords: Adsorption; Congo red; Crystal violet; Trichoderma reesei; AQUEOUS-SOLUTIONS; ADSORBENT; POWDER; Biotechnology & Applied Microbiology; Engineering